From Sales to SAervice: Driving Customer Engagement (Family Business) - Sancheti, Sakshi (ATLAS SkillTech University, 2025)
Over the past three months working in our family's wholesale tractor distribution business, I've gained a new appreciation for the complexity of our industry. Globally, we're seeing significant shifts that are reshaping how we operate. One major trend I've observed is the increasing consolidation among distributors. For example, in the US, companies like Deere & Company and AGCO Corporation have been expanding through acquisitions. This consolidation is driven by the need for greater efficiency and bargaining power with both manufacturers and dealers. It's creating challenges for smaller distributors like us, as we now compete with these larger entities that have more resources and a wider reach. Technology adoption is another crucial factor. Many global distributors are investing heavily in advanced inventory management systems and predictive analytics. For instance, I recently read about how CNH Industrial has implemented AI-driven demand forecasting. This kind of technology allows for more accurate inventory management and reduced downtime, but it also requires significant investment that smaller players might struggle to match.
Project Report on From Sales to Service: Driving Customer Engagement (Family Business) (2023-2025) Under the Guidance of Prof. Neha Karnik
Keywords: wholesale tractor; distribution business; Deere & Company; predictive analytics; CNH Industrial; AI-driven; Technology